Analisis Finansial Usaha Budidaya Lebah Madu Apis Cerana Fabr. di Dusun Sidomukti Desa Buana Sakti Kecamatan Batanghari Kabupaten Lampung Timur - Nanda Kurnia Sari; Rommy Qurniati; Rudi Hilmanto (Department of Forestry, Faculty of Agriculture, University of Lampung, 2013)
Honey consumption in Indonesia 10 gr/capital/year, nevertheless the honey production only 3 gr/capital/year (Murtidjo, 2011). Due to the highest demand of honey so it is needed honey bee enterprises. The purpose of this research was to know on financial feasibility of the Apis cerana Fabr. honey bee enterprises. The research was conducted at Sub Village Sidomukti Village Buana Sakti Sub District Batanghari East Lampung on March - April 2012 used method interview with questionnaires and observation-directly used R/C Ratio and BEP (Break Event Point). The results showed that the Apis cerana Fabr. honey bee enterprises in Sub Village Sidomukti using stup and glodok (traditional stup). Based on economic life stup and glodok for two years so financially viable honey bee enterprises performed using stup media with the value of R/C ratio > 1 is 1,616 with number to be produced to reach the breakevent point were 75 stup or at price Rp 174.807,94/stup so the honey bee farmers will get benefit of Apis cerana Fabr. honey bee enterprises. Keywords: Apis cerana Fabr., financial analysis, honeybee